Chronic and reactivated dengue infection in an immunocompromised host: insights from a case report - Ludovic Di Ascia; Etienne Frumence; Nicolas Traversier; Cécile Saint-Pastou; Gilda Grard; Henri Vacher-Coponat; Xavier de Lamballerie; Marie-Christine Jaffar-Bandjee (Tropical Medicine and Health)
Abstract Background Dengue, a viral infection transmitted by mosquitoes, is a growing global health concern, particularly as its spread now puts half of the world’s population at risk. While dengue usually resolves after the primary infection, persistent or chronic cases can occur in immunocompromised individuals. Case presentation This case study reports a 43-year-old woman with lupus nephritis and end-stage kidney disease who experienced symptomatic dengue reactivation nearly three years after her initial infection. Despite low viral loads, dengue RNA was detectable in her blood multiple times between 32 and 34 months after the initial detection. Genomic analysis confirmed that the same DENV-1 strain persisted, suggesting chronic infection rather than reinfection. The patient's immunosuppressive treatments, including rituximab, likely impaired her immune response to the initial infection, contributing to viral persistence. Additionally, her profound immunosuppressive state at the time of reactivation, potentially exacerbated by coinfections, may have triggered the virus to re-emerge. Conclusion This case highlights the rare but clinically relevant possibility of chronic dengue infection in immunocompromised patients. The confirmed persistence of the same viral strain over nearly three years challenges the conventional view of dengue as a strictly acute infection. It raises concern about the potential for reintroduction and re-emergence of previously circulating strains, as well as the detrimental tissue consequences of chronic infection by the virus. These findings have important implications for clinical management, diagnostic strategies, and public health surveillance, and underscore the need for further research to better understand the mechanisms of dengue chronicity—particularly those involving viral immune evasion and host immune dysfunction.